Sonpur excavations, 1956 and 1959-1962 - Sinha, Bindeshwari Prasad, 1919- (Directorate of Archaeology and Museums, Bihar, 1977)
Account of the archaeological excavations carried out at Sonpur, District Gaya, Bihar.